Variations in impacted mandibular permanent molars: Report of three rare cases - Manjiri Joshi; Vikrant Kasat (Wolters Kluwer Medknow Publications, 2011)
The impaction of permanent teeth is not uncommon, but few permanent teeth are rarely impacted like mandibular first and second molars. Though third molars are commonly impacted, inversely impacted mandibular third molars are very rare. Here, we report three unusual cases of impacted mandibular molars accidentally diagnosed on conventional radiographs.